Pertanggungjawaban Pidana Mengenai Tanah yang Dikuasai Orang Lain Tanpa Hak Dalam Peraturan Perundang-Undangan - Irene Putri Kartikasari Siregar; Syafruddin Kalo; Madiasa Ablisar; Dedi Harianto (Universitas Sumatera Utara, 2019)
Abstract. For Indonesia, the land has a very close relationship yam and are eternal, so that the position of land for the Indonesian nation is a unified whole that cannot be separated from each other. There is a banontheuse of land without permission is entitled to attorneys, because there are still individuals or groups who control the land without permission are entitled to power. This led to the need to beassessed on the elements of the crime of possession of land without rights. Implementation of liability offenses charged to individuals or groups who control the land without right. This study is normative, descriptive and analytical explained as well as analyzing aphenomenon that a criminal offense and accountability of the land controlled by another person without rights.There sults showed, elements of the crime of possession of land without the rights stipulated in the legislation contained in Article 385 of the Criminal Code determines the prohibition for anyone to master, sell, lease, exchange or makes debtburden (mortgaged) land that is not right as guarantee. element